Augmented Reality (AR) Marketing and Consumer Response: A Study in the Retail Industry in Indonesia - Arnold, Miracle; Rahayu, Fatik (Advances in Management & Financial Reporting, 2026)
Purpose: This study analyzes the effect of Augmented Reality (AR) stimuli, consisting of vividness, augmentation, product informativeness, and personalized recommendations, on consumers' internal responses (enjoyment, immersion, perceived usefulness, and choice confidence) and their impact on purchase intention in the context of e-commerce in Indonesia. Research design and methodology: The study used a quantitative approach with Structural Equation Modeling (SEM). Data were collected via an online survey of 228 e-commerce users in Indonesia who had used AR features, enabling comprehensive testing of causal relationships among constructs. Findings and discussion: The results show that vividness and augmentation increase enjoyment, while augmentation also strengthens immersion and choice confidence. Personalized recommendations positively affect perceived usefulness. Conversely, product informativeness tends not to support the strengthening of internal responses and, in some relationships, shows a negative direction. The findings confirm that perceived usefulness and immersion are the main determinants of purchase intention, so that cognitive mechanisms and immersive experiences are more crucial than affective responses alone. Implications: Theoretically, this study reinforces the Stimulus–Organism–Response (SOR) model in AR marketing. In practice, companies need to prioritize strengthening augmentation and personalization, and curating product information to reduce cognitive load and optimize purchase intent.